The Enlightment / An Evaluation of Its Assumptions, Attitudes and Values - Hampson Norman (Penguin Books, 1990)
The contemporary social and political climate, in which ideas could travel from the salons of Paris to the court of Catherine the Great - but less easily from a master to his servant. Preface, Introduction: The Intellectual Background to the Eighteenth Century, A New Heaven and a New Earth, Not Peace but a Sword, Appendices, Index.